Community Engagement in Schools : Evidence from a Field Experiment in Pakistan - Asim, Salman (World Bank, Washington, DC, 2020)
This paper presents the results of a field experiment in rural Sindh, Pakistan, where half of the school-age children (ages 6-10 years) are out of school. The study tests simple and low-intensity approaches to strengthen engagement of communities with schools: face-to-face dialogue at externally facilitated community meetings, and ongoing, anonymous dialogue via text messages. The interventions increased communities' interest in education as measured through an improvement in the number of functioning schools and, in the case of the text message treatment, substantial gains in retention of students in grades 2, 3, and 4. On the supply side, the schools significantly increased staffing and the share of one-teacher schools was reduced; however, teacher absenteeism increased, and there was no substantial impact on basic school infrastructure. Elections and capacity building for school committees were implemented in a cross-over experimental design. The intervention undermined the participation of communities in meetings and reduced impacts on all indicators except new admissions and availability of toilets in schools. No evidence is found of impact on measured test scores for any intervention.